Household's portfolio structure in Germany - analysis of financial accounts data 1959-2009 - Fred Ramb; Michael Scharnagl (European Central Bank (ECB), 2011)
Based on a Financial Almost Ideal Demand System (FAIDS), this paper investigates the wealth structure of German households. The long-run wealth elasticities and interestrate elasticities were calculated using a unique new quarterly financial accounts macrodata set which covers the period from 1959 to 2009 and contains a portfolio of eight different financial assets. Descriptive analysis shows that all financial assets were characterized by substantial volatility of their weight in the portfolio of households. We found that portfolio shifts in the long run are determined significantly by changes in interest rates. The estimated model provides evidence that currency (and transferable deposits) is mainly a substitute for other assets and time deposits are typically a complement. Wealth elasticity is for most assets around unity.
Keywords: E21; G11; C32; 330; financial wealth; household; portfolio structure